Performance evaluation and energetics of different type of pre-germinated rice seeders: Energetics of different type of pre-germinated rice seeders - Borkar, Narayan; Patel, Shiv Prasad; Guru , Prabhat Kumar; M. Sivashankari (ORYZA-An International Journal of Rice, 2025)
The mechanization of rice cultivation leads to higher productivity and results in higher returns to farmers. For rice crop, pre-germinated seed sowing by a drum seeder is one of the best options to eliminate the broadcasting method. The power-operated cylindrical drum, conical drum, and cup-type seeder were evaluated in comparison to manually operated six-row cylindrical drum, four-row conical drum and two-row cup-type seeder for consecutive Rabi seasons. Important machine performance parameters viz. field capacity, speed of operation, labor required, field efficiency, energy indices, economic parameters viz. cost of sowing, and crop yield were observed. Results showed that the minimum time required for a power-operated eight-row cup-type seeder was 5.75 ha h-1, while the maximum field efficiency for power power-operated eight-row conical drum seeder was 73.75 percent. The lowest input energy for a manually operated six-row cylindrical drum seeder was 629.46 MJ ha-1. The output energy for the manually operated two-row cup-type seeder was 134848 MJ ha-1. The highest specific energy for power operated seeder was 0.24MJ kg-1 and the maximum energy productivity for a manually operated four-row conical drum seeder was 6.59 kg MJ-1 compared to 4.39 kg MJ-1 for power operated eight-row conical seeder. The highest energy profitability recorded for a manually operated four-row conical drum seeder was 197.18 per cent. The lowest labour cost for an eight-row power-operated cup-type seeder was 6.65 $ ha-1 while the highest for a two-row cup-type seeder was 26.78 $ ha-1. The minimum machine operational cost for a manually operated six-row cylindrical seeder was 10.66 $ ha-1 compared to power-operated eight-row cylinderical seeder was20.13 $ ha-1. There was no significant difference in the yield of rice was observed among different treatments. The manually operated seeders were more energy efficient than power-operated seeders but power operated seeder has high field capacity and require less sowing time as compared to manual-operated seeders.